Antimicrobial Activity of Human Fetal Membranes: From Biological Function to Clinical Use - Ramuta, Taja Železnik; Šket, Tina; Starčič Erjavec, Marjanca; Kreft, Mateja Erdani (Frontiers in Bioengineering and Biotechnology, 2021)
The fetal membranes provide a supportive environment for the growing embryo and later fetus. Due to their versatile properties, the use of fetal membranes in tissue engineering and regenerative medicine is increasing in recent years. Moreover, as microbial infections present a crucial complication in various treatments, their antimicrobial properties are gaining more attention. The antimicrobial peptides (AMPs) are secreted by cells from various perinatal derivatives, including human amnio-chorionic membrane (hACM), human amniotic membrane (hAM) and human chorionic membrane (hCM). By exhibiting antibacterial, antifungal, antiviral and antiprotozoal activities and immunomodulatory activities, they contribute to ensuring a healthy pregnancy and preventing complications. Several research groups investigated the antimicrobial properties of hACM, hAM and hCM and their derivatives. These studies advanced basic knowledge of antimicrobial properties of perinatal derivatives and also provided an important insight into the potential of utilizing their antimicrobial properties in a clinical setting. After surveying the studies presenting assays on antimicrobial activity of hACM, hAM and hCM, we identified several considerations to be taken into account when planning future studies and eventual translation of fetal membranes and their derivatives as antimicrobial agents from bench to bedside. Namely, 1) the standardization of hACM, hAM and hCM preparation to guarantee rigorous antimicrobial activity, 2) standardization of the antimicrobial susceptibility testing methods to enable comparison of results between various studies, 3) investigation of the antimicrobial properties of fetal membranes and their derivatives in the in vivo setting and 4) designation of donor criteria that enable the optimal donor selection. By taking these considerations into account, future studies will provide crucial information that will enable reaching the optimal treatment outcomes using the fetal membranes and their derivatives as antimicrobial agents.